LEGAL STUDY ON THE ESTABLISHMENT OF A FOUNDATION AS A LEGAL ENTITY LEGAL ANALYSIS NUMBER 28 OF 2004 CONCERNING FOUNDATIONS - Sardi; Henry Aspan (Universitas Efarina, 2023)
This research was carried out with the aim of finding out the objectives of a foundation as a private legal entity according to Law Number 28 of 2004 and what are the requirements for establishing a foundation as a legal entity. By using normative juridical research methods, it can be concluded: 1. The aims of foundations as private legal entities according to Law Number 28 of 2004 are social, religious and humanitarian. Social goals: establishing formal and non-formal education, orphanages, retirement homes, nursing homes, hospitals, polyclinics and laboratories. Religious objectives: establishing facilities for worship, receiving and distributing alms. Humanitarian goals: providing assistance to victims of natural disasters, providing assistance to the homeless, the poor and homeless, preserving the environment. What are the requirements for establishing a foundation as a legal entity? How is the legal study aimed at establishing a foundation as a legal entity? Analysis of Law Number 28 of 2004 concerning Foundations? namely: founded by one or more people; there is wealth that is separated from the wealth of the founder; must be done with a notarial deed and made in Indonesian; must obtain approval from the Minister of Law and Human Rights; announced in the Supplement to the State Gazette of the Republic of Indonesia; must not use a name that has been legally used by another foundation, or is contrary to public order and/or morality; The name of the foundation must be preceded by the word